2022
DOI: 10.1101/2022.03.28.485354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell type profiling in salamanders identifies innovations in vertebrate forebrain evolution

Abstract: The evolution of advanced cognition in vertebrates is associated with two independent innovations in the forebrain: the six-layered neocortex in mammals and the dorsal ventricular ridge (DVR) in sauropsids (reptiles and birds). How these novelties arose in vertebrate ancestors remains unclear. To reconstruct forebrain evolution in tetrapods, we built a cell type atlas of the telencephalon of the salamander Pleurodeles waltl. Our molecular, developmental, and connectivity data indicate that parts of the saurops… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 84 publications
4
29
0
Order By: Relevance
“…In a recent scRNAseq study (Woych et al 2022), we identified 114 clusters of neurons sampled from the adult telencephalon of the urodele amphibian Pleurodeles waltl . Of these, 41 clusters were annotated as telencephalic glutamatergic neurons, on the basis of the expression of marker genes including the transcription factors Foxg1, Emx1, Tbr1 , and Neurod2 , the glutamate transporters Slc17a6 and Slc17a7 , and for the lack of expression of diencephalic markers (Woych et al 2022). After staining brain sections or whole-mount brain preparations for cluster-specific marker genes, we assigned a regional identity to each of these clusters.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent scRNAseq study (Woych et al 2022), we identified 114 clusters of neurons sampled from the adult telencephalon of the urodele amphibian Pleurodeles waltl . Of these, 41 clusters were annotated as telencephalic glutamatergic neurons, on the basis of the expression of marker genes including the transcription factors Foxg1, Emx1, Tbr1 , and Neurod2 , the glutamate transporters Slc17a6 and Slc17a7 , and for the lack of expression of diencephalic markers (Woych et al 2022). After staining brain sections or whole-mount brain preparations for cluster-specific marker genes, we assigned a regional identity to each of these clusters.…”
Section: Resultsmentioning
confidence: 99%
“…The dataset was generated from single-cell RNA sequencing of the Pleurodeles waltl brain as described in (Woych et al 2022). For in-depth analysis of the amygdala, the data were subsetted, and heterogeneous clusters (TEGLU25, 35 and 38) were subclustered based on differential gene expression.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations